Perbandingan kuat tekan beton menggunakan pasir pantai dengan bahan aditif dan tanpa aditif serta perendaman air tawar dan air laut - Harits, Emil; Satria, Muhammad Fiqri; Wattini, Wattini; Utomo, Satriyo (Construction and Material Journal, 2025)
This study evaluates the effect of silica fume additives on concrete compressive strength and concrete characteristics. Silica fume is known to improve the quality of concrete through pozzolanic reactions that improve microstructure and reduce porosity. In this study, concrete with silica fume content of 6%, 7%, 8%, and 9% of the weight of cement was produced and tested. Testing was carried out at the age of 14 days to assess the compressive strength of concrete and concrete density. With the maximum increase recorded in the mixture with 8% silica fume in construction, concrete is an important component. This study indicates that the addition of silica fume additives to concrete can increase the compressive strength of the material. Based on this, ordinary concrete is not very resistant to sulfuric acid solutions found in seawater. After 14 days of immersion, the effects of sulfuric acid began to reduce the compressive strength of concrete in both freshwater and seawater, with normal concrete dropping from 19.60 MPa to 19.42 MPa, 6% silica fume concrete in freshwater from 20.04 MPa to 19.91 MPa, seawater concrete with 7% silica fume from 20.09 MPa to 19.95 MPa, with 8% silica fume from 20.22 MPa to 20.10 MPa, and with 9% silica fume from 20.18 MPa to 20.06 MPa. In conclusion, silica fume additives can increase the compressive strength of concrete; the higher the percentage of silica fume additives used, the higher the compressive strength.